Variation of gonadal cycle of the american oyster, Crassostrea virginica (Ostreoida: Ostreidae) as a function of height in Tamiahua Lagoon, Veracruz, Mexico - Ascencio A., Luis Alfonso (2014)
The American oyster, Crassostrea virginica is one of the most important fishery resources of the Gulf of Mexico, where it has been classified as “resource exploited at maximum”. Since 1994state authorities set a minimum extraction shell length of 70 mm (adult size); this was based on population studies alone. We compare the gonadal cycle of subadults oysters with adult organisms. From January to December 2011, 90 oysters were collected monthly in Tamiahua Lagoon, Veracruz and classified as subadults (50-69mm; 75% of sample) and adults (≥70mm).Histological gonad sections were classified in four categories: rest, gametogenesis, maturation and release of gametes. In subadults, the rest stage had two peaks (January 22% and June 13%), and gametogenesis between January and July (22-74%). Maturation was observed in July, August and September (40, 64 and 41% respectively) and release in October (66%) and November (45%). Correspondingly, adults were resting in January and June (17 and 13%), and January-July gametogenesis (56-88%), matured in August and September (64 and 42%) and released gametes in September and October (54 and 70%). The gametogenic cycle was similar in subadults and adults: the species breeds from sizes equal or smaller than 50 mm and this should be considered by authorities. Rev. Biol. Trop. 62 (Suppl. 3): 201-206. Epub 2014 September 01.